(untitled) (Research, Society and Development, 2021)
The 4th Industrial Revolution (4IR), characterized by the combination of different technologies, in several degrees of maturity, generates a set of innovation opportunities in the industry. This revolution, known as Industry 4.0, originated in Germany, within a national strategy to make the country a leader in technology, aiming to strengthen its global competitiveness. The current technological environment of Industry 4.0 makes use of interconnected cyber-physical systems through a set of enabling technologies. With the connectivity of these systems, Cyber Security challenges arise, making these issues a top concern for business leaders. Faced with a scenario for the protection of data and information, this research carried out a bibliometric study on the scientific production related to Cyber Security in Industry 4.0, using a quantitative-qualitative approach to measure publications and their characteristics. The analysis and discussion of the results made it possible to identify the research areas of the publications, the periodicals with the largest number of publications, the authors with the most cited works, the countries and institutions with the most relevant research on the topic, and the representativeness of the keywords used in publications identified in the Web of Science and Scopus databases.